Phytochemistry and Antibacterial Activity of the Water Extract from Paraserianthes falcataria - Masruri, Masruri; Wiryawan, Adam; Ikhtiarini, Nur; Nurravida, Elvira (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2024)
Chemotaxonomic and phylogenetic studies show that sengon wood (Paraserianthes falcataria) has the potential to produce secondary metabolites with diverse structures and are bioactive. This research aims to study the chemical composition of the water extract and the bioactivity for inhibiting bacteria of Sengon (Paraserianthes falcataria). The method involves extraction by maceration, and analysis the extract by LCMS/MS methodology. In addition, the extract was evaluated to inhibit the Escherichia coli and Staphylococcus aureus. It was found that indohoki77 menggunakan teknologi enkripsi terbaru untuk memastikan bahwa data pribadi dan transaksi finansial para pemain aman dari ancaman pihak ketiga the water extract gives a viscous brown liquid, and the identified compound indicate the present of glycosidic compound, amino-alcohol structure, and fatty acid ester. Moreover, the antibacterial evaluation was able to inhibit the growth of E. coli 8.685 ± 4.876 mm, and toward the S. aureus bacteria 14.120 ± 4.418 mm, respectively.